2014
DOI: 10.1136/jnnp-2013-307223
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive correlates in amyotrophic lateral sclerosis: a population-based study in Italy

Abstract: About 50% of Italian patients with ALS had some degree of cognitive impairment, in keeping with a previous Irish study, despite the largely different genetic background of the two populations. The lower educational attainment in patients with ALS-FTD indicated a possible role of cognitive reserve in ALS-related cognitive impairment. ALS-ECI and ALS-NECI may represent discrete cognitive syndromes in the continuum of ALS and FTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
205
5
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(230 citation statements)
references
References 28 publications
15
205
5
5
Order By: Relevance
“…The study showed a high prevalence of ALS patients with either cognitive or behavioral impairment, in line with a growing literature of population-based studies [3,4,21,22]. In our series, 10.8% of patients fulfilled criteria for a behavioral variant FTD diagnosis, almost half of the patients presented either cognitive (ALS-ci) or behavioral (ALS-bi) impairment, and 39.2% showed no disturbances.…”
Section: Discussionsupporting
confidence: 70%
“…The study showed a high prevalence of ALS patients with either cognitive or behavioral impairment, in line with a growing literature of population-based studies [3,4,21,22]. In our series, 10.8% of patients fulfilled criteria for a behavioral variant FTD diagnosis, almost half of the patients presented either cognitive (ALS-ci) or behavioral (ALS-bi) impairment, and 39.2% showed no disturbances.…”
Section: Discussionsupporting
confidence: 70%
“…Previous Table 1 Demographic and clinical characteristics of patients with amyotrophic lateral sclerosis (ALS) with (C9Pos) and without (C9Neg) the pathogenic C9orf72 expansion descriptions of C9Pos patients are relatively small and do not include comparisons to a large, unselected cohort of C9Neg patients (table e-1). 3,23 Other than the presence of a family history of ALS and increased prevalence of FTD, these 2 groups were clinically similar at presentation to the clinic. The distribution of site of onset of disease in our cohort of C9Pos patients closely mirrored that of C9Neg patients and was typical of other ALS cohorts.…”
Section: Demographic and Clinical Information Acquisitionmentioning
confidence: 98%
“…Our finding of reduced overall survival in our C9Pos population compared to C9Neg patients is consistent with the published experience from other C9Pos cohorts. 3,4,8,22,23 In addition, we used a Cox proportional hazards model to determine the influence of variables other than the C9 mutation, such as Figure 1 Flowchart of family history of amyotrophic lateral sclerosis (ALS) in screened cohort A total of 781 cases were screened for the C9orf72 expansion. Of those 781, 90 cases had a known family history of ALS, while 691 had no known family history of ALS.…”
Section: Demographic and Clinical Information Acquisitionmentioning
confidence: 99%
“…Of these, approximately one third or more of familial ALS (fALS) can be attributed to the C9orf72 mutation [15]; SOD1 mutation accounts for 20 % of fALS, while mutations of TAR DNA-binding protein (TARDBP) (5-10 %), FUS RNA-binding protein (FUS) (5 %), are less frequent [14]. In one cohort of ALS-FTD patients, 26 % were found to be C9orf72 positive (6 out of 23 subjects) [16].…”
Section: Diagnosis and Geneticsmentioning
confidence: 97%